Halide metathesis in overdrive: mechanochemical synthesis of a heterometallic group 1 allyl complex - Koby, Ross F.; Rightmire, Nicholas R.; Schley, Nathan D.; Hanusa, Timothy P.; Brennessel, William W. (Beilstein Journal of Organic Chemistry, 2019)
As a synthesis technique, halide metathesis (n RM + M'Xn → RnM' + n MX) normally relies for its effectiveness on the favorable formation of a metal halide byproduct (MX), often aided by solubility equilibria in solution. Owing to the lack of significant thermodynamic driving forces, intra-alkali metal exchange is one of the most challenging metathetical exchanges to attempt, especially when conducted without solvent. Nevertheless, grinding together the bulky potassium allyl [KA']∞ (A' = [1,3-(SiMe3)2C3H3]–) and CsI produces the heterometallic complex [CsKA'2]∞ in low yield, which was crystallographically characterized as a coordination polymer that displays site disorder of the K+ and Cs+ ions. The entropic benefits of mixed Cs/K metal centers, but more importantly, the generation of multiple intermolecular K…CH3 and Cs…CH3 interactions in [CsKA'2]∞, enable an otherwise unfavorable halide metathesis to proceed with mechanochemical assistance. From this result, we demonstrate that ball milling and unexpected solid-state effects can permit seemingly unfavored reactions to occur.
Keywords: caesium; entropy; intermolecular forces; mechanochemistry; metathesis; potassium

Organometallics - Elschenbroich, C. (VCH Publishers, 2006)

Hard and Soft Acids and Bases - Pearson, R. G. (Dowden, Hutchinson & Ross, 1973)

(untitled) - Borisov, A. P.; Makhaev, V. D.; Usyatinskii, A. Y.; Bregadze, V. I. (Izv. Akad. Nauk, Ser. Khim., 1993)

(untitled) - Gomes, C. S. B.; Gomes, P. T.; Duarte, M. T. (J. Organomet. Chem., 2014)

(untitled) - Makhaev, V. D.; Borisov, A. P.; Petrova, L. A. (J. Organomet. Chem., 1999)

(untitled) - Boyde, N. C.; Rightmire, N. R.; Bierschenk, E. J.; Steelman, G. W.; Hanusa, T. P.; Brennessel, W. W. (Dalton Trans., 2016)

(untitled) - Boyde, N. C.; Steelman, G. W.; Hanusa, T. P. (ACS Omega, 2018)

(untitled) - Peters, D. W.; Blair, R. G. (Faraday Discuss., 2014)

(untitled) - Boyde, N.; Rightmire, N.; Hanusa, T.; Brennessel, W. (Inorganics, 2017)

(untitled) - Rightmire, N. R.; Hanusa, T. P.; Rheingold, A. L. (Organometallics, 2014)

(untitled) - Koby, R. F.; Hanusa, T. P.; Schley, N. D. (J. Am. Chem. Soc., 2018)

(untitled) - Allred, A. L.; Rochow, E. G. (J. Inorg. Nucl. Chem., 1958)
The Allred-Rochow electronegativities of the alkali metals, for example, vary only over a range of 0.86–1.01.

(untitled) - Chmely, S. C.; Hanusa, T. P. (Eur. J. Inorg. Chem., 2010)

(untitled) - Solomon, S. A.; Layfield, R. A. (Dalton Trans., 2010)

(untitled) - Boche, G.; Fraenkel, G.; Cabral, J.; Harms, K.; Van Eikema Hommes, N. J. R.; Lohrenz, J.; Marsch, M.; Schleyer, P. v. R. (J. Am. Chem. Soc., 1992)

(untitled) - McMillen, C. H.; Gren, C. K.; Hanusa, T. P.; Rheingold, A. L. (Inorg. Chim. Acta, 2010)

(untitled) - Gren, C. K.; Hanusa, T. P.; Rheingold, A. L. (Main Group Chem., 2009)

(untitled) - Quisenberry, K. T.; Gren, C. K.; White, R. E.; Hanusa, T. P.; Brennessel, W. W. (Organometallics, 2007)

(untitled) - Harvey, M. J.; Hanusa, T. P.; Young, Jr., V. G. (Angew. Chem., Int. Ed., 1999)

(untitled) - Speight, I. R.; Chmely, S. C.; Hanusa, T. P.; Rheingold, A. L. (Chem. Commun., 2019)
Alkali metal fluorides can be useful as reagents if the thermodynamics of the system are appropriately configured, however. For example, the reaction of [LiN(SiMe3)2] with CsF works to produce the products [CsN(SiMe3)2] with LiF in high yield because the relative heats of formation (∆H°f) of CsF and LiF (−554 and −616 kJ mol−1, respectively) provide a net driving force of −62 kJ mol–1. See: Ojeda-Amador, A. I.; Martínez-Martínez, A. J.; Kennedy, A. R.; O’Hara, C. T. Inorg. Chem. 2016, 55, 5719–5728. doi:10.1021/acs.inorgchem.6b00839

(untitled) - Simpson, C. K.; White, R. E.; Carlson, C. N.; Wrobleski, D. A.; Kuehl, C. J.; Croce, T. A.; Steele, I. M.; Scott, B. L.; Young, V. G.; Hanusa, T. P.; Sattelberger, A. P.; John, K. D. (Organometallics, 2005)

(untitled) - Ma, J. C.; Dougherty, D. A. (Chem. Rev., 1997)

(untitled) - Ojeda-Amador, A. I.; Martínez-Martínez, A. J.; Robertson, G. M.; Robertson, S. D.; Kennedy, A. R.; O'Hara, C. T. (Dalton Trans., 2017)

(untitled) - Solomon, S. A.; Muryn, C. A.; Layfield, R. A. (Chem. Commun., 2008)

(untitled) - Shi, Y. X.; Xu, K.; Clegg, J. K.; Ganguly, R.; Hirao, H.; Friščić, T.; García, F. (Angew. Chem., Int. Ed., 2016)

The NBS Tables of Chemical Thermodynamic Properties - Wagman, D. D.; Evans, W. H.; Parker, V. B.; Schumm, R. H.; Halow, I. (American Chemical Society and the American Institute of Physics for the National Bureau of Standards, 1982)

(untitled) - Becke, A. D. (Phys. Rev. A, 1988)

(untitled) - Perdew, J. P.; Wang, Y. (Phys. Rev. B, 1992)

(untitled) - Grimme, S.; Antony, J.; Ehrlich, S.; Krieg, H. (J. Chem. Phys., 2010)

(untitled) - Garcés, J. (Appl. Phys. Lett., 2010)

(untitled) - Kleeberg, C.; Grunenberg, J.; Xie, X. (Inorg. Chem., 2014)

(untitled) - Westerhausen, M.; Oßberger, M. W.; Alexander, J. S.; Ruhlandt-Senge, K. (Z. Anorg. Allg. Chem., 2005)

(untitled) - Kopp, M. R.; Neumüller, B. (Z. Anorg. Allg. Chem., 1998)

Cambridge Structural Database (2018)
Release Nov. 2018.